What do Consumers really want? Online Vs Offline Shopping for Fashion Products - Sisca Sisca; Andy Wijaya; Ernest Grace; Debi Eka Putri; Novelyne Sidabutar (Research Synergy Foundation, 2022)
Digitalization has changed human behavior in carrying out various activities, one of which is consumer behavior in shopping. Nowadays, many consumers often make purchases of products online. However, certain products actually require a more in-depth product evaluation before consumers decide to buy the product, which can only be done by shopping offline, one of them is fashion products. This research is conducted to identify the factors that motivate consumers in Indonesia to shop online or offline and determine whether there are differences between these motivating factors based on the demographic characteristics of consumers. Data collection is carried out by distributing questionnaires online through whatsapp and telegram groups during June-July 2021, which resulted in 162 responses. Chi-Square, Mann-Whitney, and Kruskal-Wallis tests are used to test the hypothesis. The results prove that the relationship between the motivating factors to shop offline and preferred shopping method with the consumer demographic characteristics, most of them show insignificant results. Different results are shown in the relationship between the motivating factors to shop online with the consumer demographic characteristics, which most of them show significant results (age group, marital status and education level). Furthermore, research data also shows that more than half of the respondents still prefer to shop for fashion products offline rather than online although in the Covid-19 pandemic situation because they want to evaluate the product physically. Suggestions for future researchs to adopt a more representative sampling technique to replicate this research and adopt different product categories to explore how consumers behave in other product categories. This research provides a deeper understanding of consumer shopping behavior for fashion products both online and offline as well as provides an overview that there is still a future for offline fashion product stores to survive in competition with online stores by improving themselves to deal with consumer purchases in this new normal era.